Prognostic Factors Influencing Infectious Complications after Cytoreductive Surgery and HIPEC: Results from a Tertiary Referral Center. (2nd May 2019) - Cardi, Maurizio; Sibio, Simone; Di Marzo, Francesco; Lefoche, Francesco; d'Agostino, Claudia; Fonsi, Giovanni Battista; La Torre, Giuseppe; Carbonari, Ludovica; Sammartino, Paolo
Abstract : Background . Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) showed promising results in selected patients. High morbidity restrains its wide application. The aim of this study was to report postoperative infectious complications and investigate possible correlations with the preoperative nutritional status and other prognostic factors in patients with peritoneal metastases treated with CRS and HIPEC. Methods . For the study, we reviewed the clinical records of all patients with peritoneal metastases from different primary cancers treated with CRS and HIPEC in our Institution from November 2000 to December 2017. Patients were divided according to their nutritional status (SGA) into groups A (well-nourished) and B/C (mild or severely malnourished, respectively). Possible statistical correlations between risk factors and postoperative complication rates have been investigated by univariate and multivariate analysis. Results . Two hundred patients were selected and underwent CRS and HIPEC during the study period. Postoperative complications occurred in 44% of the patients, 35.3% in SGA-A patients, and 53% in SGA-B/C patients. Cause of complications was infective in 42, noninfective in 37, and HIPEC related in 9 patients. Infectious complications occurred more frequently in SGA-B/C patients (32.6% vs. 9.8% of SGA-A patients). The most frequent sites of infection were surgical site infections (SSI, 35.7%) and central line-associated bloodstream infections (CLABSI, 26.2%). The most frequent isolated species was Candida (22.8%). ASA score, blood loss, performance status, PCI, large bowel resection, postoperative serum albumin levels, and nutritional status correlated with higher risk for postoperative infectious complications. Conclusions . Malnourished patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy are more prone to postoperative infectious complications, and adequate perioperative nutritional support should be considered, including immune-enhancing nutrition. Sequential monitoring of common sites of infection, antifungal prevention of candidiasis, and careful patient selection should be implemented to reduce the complication rate.